Suara Senyap Perempuan di Jalur Arang - Ka'bati, Ka'bati (Puitika, 2024)
The Minangkabau matrilineal system places women as owners of inherited land. In 1872, the Dutch colonial government began opening the Baro railway line from Sawahlunto to Teluk Bayur . This development process will involve land owned by women. This article begins with the question of how negotiations are carried out with women regarding their rights. The research was conducted using a qualitative descriptive method with a feminist perspective with the assumption that women were marginalized from history because their stories were considered unimportant. The results of the exploration of the views and imaginations remaining in women's minds show that men dominate (niniak mamak) over women in the negotiation room. This domination is possible because women represent their voices in negotiating and deciding matters to men in the hope that men will defend their interests. On the other hand, men were also faced with a new, more individual worldview introduced by the colonialists so that they could no longer uphold the interests of their people.